The Effect Of Blanket Warmers On Hypothermia In Patients Under General Anesthesia In The Recovery Room Of Siaga Medika Hospital, Purbalingga - Suci Sri Andriyani; Endiyono Endiyono (International Journal of Health Engineering and Technology, 2026)
Postoperative hypothermia is a significant clinical complication for patients undergoing general anesthesia, often resulting from impaired thermoregulation and cold environmental exposure in the operating theater. This study aimed to evaluate the influence of a blanket warmer on body temperature stabilization in postoperative patients experiencing hypothermia in the recovery room. A quantitative study with a pre-experimental one-group pretest-posttest design was conducted at RSU Siaga Medika Purbalingga. The study included 40 patients selected via purposive sampling who met the inclusion criteria. Body temperature was measured before and at 5, 10, and 15-minute intervals following the application of a blanket warmer. The data were analyzed using the Kruskal-Wallis test. The results demonstrated that the mean temperature increased significantly from 34.71℃ at baseline to 36.35℃ after 15 minutes of intervention (p<0.001). These findings indicate that the blanket warmer is highly effective in increasing core body temperature and facilitating a return to normothermia within the recovery phase. Implementing this non-pharmacological intervention as a standardized nursing protocol is essential to enhance patient comfort, reduce recovery duration, and minimize anesthesia-related complications.